ADVANCES IN CARE FOR PATIENTS WITH STROKE: INTEGRATIVE REVIEW - Alves Torquato, Beatriz; Lemos de Almeida, Elisdárquia; Lucas Avinte Bentes, Jean; Virna Monteiro de Abreu, Luisa; Soares, Liliane; de Sousa Martins, Nataly; Melo Lopes, Rafael; Gondim Moreira, Raquel (Health and Society, 2024)
Stroke is a medical emergency characterized by the sudden onset of neurological deficits, classified as either ischemic, caused by obstruction of blood flow, or hemorrhagic, due to the rupture of a cerebral vessel. It remains one of the leading causes of death and disability worldwide, with early diagnosis being crucial for improving patient outcomes. This study presents an integrative review of advancements in stroke care, emphasizing the importance of prompt treatment to reduce complications and enhance functional independence. The review analyzed 14 relevant studies from the last five years, sourced from databases like PubMed and Google Scholar. Key findings highlight the significance of rapid hospital arrival, early use of MRI to predict cognitive impairments, and clear communication regarding prognosis. The study also identified barriers in patient care flow, indicating a need for Continuing Education and improved coordination within the Emergency Care Network. Effective integration among healthcare professionals is essential to optimize care quality and rehabilitation outcomes for stroke patients.